/mu/ and mu-reduction in Nyakyusa. Issue 2 (3rd July 2019) - Persohn, Bastian
Abstract : This article discusses the sequence /mu/ in Nyakyusa. The absence of its degree 2-vowel counterpart /mʊ/ is discussed, which is analysed as the effect of a constraint against this specific sequence. This forms part of a larger series of peculiar constraints against /(V)NVdegree2 / sequences in Nyakyusa. Based on an overview of mu-reduction across Bantu (a type of syncope, by which the high vowel of certain prefixes deletes), the specific phonological and morphosyntactic conditions that determine the application of mu-reduction are examined for each relevant prefix. The findings include that mu-reduction in Nyakyusa is independent of syllable count and, where it applies, regularly induces regressive assimilation of the nasal as well as post-nasal hardening. However, not all prefixes of the shape mu - undergo reduction, and the behaviour of the prefixes of locative noun class 18 is determined by phonological as well as by morphological context.